The dog and the piglet : and four other true stories of animal friendships - Holland, Jennifer S. (New York : Workman Pub., 2012)
Presents five stories about animals who have forged unlikely, abiding bonds with other animals of different species.
7 and up.
Keywords: Social behavior in animals -- Juvenile literature; Friendship -- Juvenile literature; Animals -- Juvenile literature; Social behavior in animals; Friendship; Animals